The impact of Bacillus Calmette-Guérin (BCG) vaccination on the course of COVID-19 - Jakub Krzysztof Gałązka (Kazimierz Wielki University, 2022)
Nowadays, Bacillus Calmette-Guérin (BCG) is the most commonly used vaccine worldwide, used typically for tuberculosis but also in non-muscle invasive bladder cancer management. Basing on previously confirmed antiviral features of BCG and first statistic data reports, BCG usage in COVID-19 prevention was claimed and its potential molecular mechanism was searched. In scientific literature there was 10 publications proving several possible mechanism of BCG interaction with SARS-CoV-2 infection immune response. The most often was cross-reactivity between various BCG and SARS-CoV-2 antigens, including those crucial for their clinical effects. In most cases, those antigens linking was shown according to bioinformatical research. According to this research, the potential role of BCG in COVID-19 management should be considered as significant, at least until the clinical trials conducted nowadays will be over.